La Diana of Montemayor as Social and Religious Teaching - Damiani, Bruno Mario (Book collections on Project MUSE., 1983)
Jorge de Montemayor's great pastoral novel La Diana (1559), one of the fountainheads of Spanish Renaissance literature, has often been regarded as a work written merely to amuse an effete courtly world. Bruno M. Damiani argues here that, far from being simply a ""pastoral dream, "" Diana has profound socio-historical and religious dimensions, and that Montemayor's intentions in it were largely moral and instructive. The timeless, idyllic nature which forms the essence of the pastoral is, in the case of Diana, inextricably bound up with the grace and sophistication of urban Spanish culture. In